A care crisis in the Nordic Welfare states? care work, gender equality and welfare state sustainability - Dahl, Hanne Marlene; Hansen, Lise Lotte 1962-; Horn, Laura 1980- (Policy Press, 2022)
Academic experts review the impact of neoliberal politics and ideology on the status of care work in Nordic countries. They explore different understandings of the care crisis, the consequences for gender equality and the long-term sustainability of the Nordic welfare states.